(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2015)
The population decline that has been affecting Macedonian villages for over sixty years is due to people migrating from villages to cities, also known as rural flight. Some of the villages still have a few old inhabitants, however it is expected that soon after they die, those villages will meet the same destiny as the ones that have been already abandoned. After the Second World War, the industrialization motivated many of the village inhabitants to find work in the opening factories, in search of a better life. Consequently, no one was trying to improve the living conditions in the villages; therefore, people never migrated back from cities to villages. Poreche, for example, is an area with living conditions that have not been improved, while also not having good connection with the urban centres. Therefore, from the beginning of the 21st century this area has been isolated from the rest of the world. Young people usually do not like this lifestyle, so when they move to the big places because of their education and see the lifestyle the people over there lead, they have no desire to go back. Girls have it easier when it comes to staying in the cities, often enough they marry at a young age, leaving behind the boys from the villages who stay unmarried. Because of the harsh conditions, the boys find themselves in a situation where they cannot find a wife who would accept to come and live with them in the village whilst not being able to leave the villages and move to the city because of their financial problems. Eventually, most of them end up sitting in front of the village shop with a beer in their hand.